2016
DOI: 10.4240/wjgs.v8.i4.294
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy in gastric cancer: Contentious issues

Abstract: The stomach is the sixth most common cause of cancer worldwide. Surgery is an important component of the multi-modality treatment of the gastric cancer. The extent of lymphadenectomy has been a controversial issue in the surgical management of gastric cancer. The East-Asian surgeons believe that quality-controlled extended lymphadenectomy resulting in better loco-regional control leads to survival benefit in the gastric cancer; contrary to that, many western surgeons believe that extended lymphadenectomy adds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…One of them was the fact that surgeons participating in this trial had no previous experience in D2 lymphadenectomies and they were trained using video recurrence rates were also lower in D2 group. The overall 15-year survival was 21% in D1 group and 29% in D2, without statistically significant difference (p = 0.34) [4,9].…”
Section: Extent Of Lymphadenectomy For Stage Ib-iii Gastric Carcinomamentioning
confidence: 84%
See 1 more Smart Citation
“…One of them was the fact that surgeons participating in this trial had no previous experience in D2 lymphadenectomies and they were trained using video recurrence rates were also lower in D2 group. The overall 15-year survival was 21% in D1 group and 29% in D2, without statistically significant difference (p = 0.34) [4,9].…”
Section: Extent Of Lymphadenectomy For Stage Ib-iii Gastric Carcinomamentioning
confidence: 84%
“…The third landmark RCT on this subject, the Italian study, found comparable overall morbidity (12.0% in D1 vs. 17.9% in D2, p = 0.178) and no significant difference in 30-day postoperative mortality rate (3.0% in D1 vs. 2.2% in D2, p = 0.72). The essential difference was that only experienced surgeons participated in this trial and that distal pancreatectomy with splenectomy was not routinely performed [4,9]. The main conclusion is that in Western countries D2 lymphadenectomy can be safely performed in high-volume centres by experienced surgeons.…”
Section: Extent Of Lymphadenectomy For Stage Ib-iii Gastric Carcinomamentioning
confidence: 99%
“…Focusing on the extension of the lymph node dissection, nowadays the D2 lymphadenectomy with preservation of the pancreas and spleen is considered the standard of care by the guidelines of various global scientific societies [ 34 , 35 ] and it is recommended to be conducted by an experienced surgeon, especially if performed laparoscopically [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the fifth most common and third most lethal cancer worldwide, with 783,000 deaths in 2018 [1]. Gastrectomy with regional lymphadenectomy is the preferred surgical treatment for nonmetastatic gastric adenocarcinoma [2]. Despite multimodal treatment, the majority of patients with advanced nonmetastatic cancer recur with the peritoneal disease (29–56%) [3-6].…”
Section: Introductionmentioning
confidence: 99%